Efficacy and safety of extracorporeal shockwave therapy for the treatment of chronic non-bacterial prostatitis: A systematic review and meta-analysis. - Ponco Birowo; Ervandy Rangganata; Nur Rasyid; Widi Atmoko (PLoS ONE, 2020)
Purpose Chronic pelvic pain syndrome (CPPS) is one of the most common outpatient urological diagnoses, and its incidence is increasing. Extracorporeal shockwave therapy (ESWT) has been suggested for relieving local perineal symptoms associated with chronic prostatitis/CPPS. Despite several treatment methods, no causal or standardized treatment is available for CPPS. This study aimed to investigate the efficacy and safety profile of ESWT for the treatment of chronic non-bacterial prostatitis. Materials and methods Studies were collected using four search engines (Pubmed, Cochrane, ScienceDirect, and EBSCOHost), on May 16, 2020; and assessed based on predetermined inclusion and exclusion criteria. Two reviewers performed study selection. Studies were then analyzed using Review Manager 5.3 for the meta-analysis. Results Seventy-four publications were initially retrieved, and three studies were considered for both qualitative and quantitative analyses. From these studies, we found that the use of ESWT was significantly associated with decreased pain domain (mean difference: -3.93; 95% confidence interval [CI] -5.13, -2.73; p<0.001), improved urinary score (mean difference: -1.79; 95% CI -2.38, -1.21; p<0.001), improved quality of life (mean difference: -1.71; 95% CI -2.12, -1.31; p<0.001), and improved National Institutes of Health chronic prostatitis symptom index (NIH-CPSI) score (mean difference: -5.45; 95% CI -5.74, -5.16; p<0.001) after 12 weeks of treatment. Conclusion ESWT is efficacious and safe in reducing pain and improving urinary condition, NIH-CPSI score, and quality of life in patients with chronic non-bacterial prostatitis.